Clinicoepidemiological profile and outcome among children with acute encephalitis syndrome from Central India - Rashmi Bhadouriya,; Hemant Jain,; Dharmanshu Chaube,; Bharani, Anjali (Asian Journal of Medical Sciences, 2022)
Background: Acute encephalitis syndrome (AES) is defined as the acute onset of fever and a change in mental status and/or new onset of seizures (excluding simple febrile seizures) in a person of any age at any time of the year. Aims and Objectives: The objectives of the study were as follows: (a) To study clinicoepidemiological profile and outcome among children with AES admitted at M.Y.H. Hospital and MGM Medical College, Indore, M.P., and (b) to study prognostic factors associated with bad outcomes. Materials and Methods: This prospective observational study was conducted over 12 months (July 2019–August 2020) at the pediatric department of our hospital. Inclusion criteria: Inpatient children aged 6 months–14 years meeting the case definitions of acute encephalitis syndrome. Exclusion criteria: Simple febrile seizures. Results: Out of 50 AES cases, majority were between 1 and 5 years of age (40%). There were more males 31 (62%) than 19 (38%) females. Most of the cases were reported during the monsoon period 29 (58%) followed by post-monsoon 13 (26%) and pre-monsoon 8 (16%). Out of 50 cases, all had fever and altered sensorium, 37 (74%) had convulsions, 14 (28%) had vomiting, and 9 (18%) had headache. Out of 50 cases, 42 (84%) had viral etiology including 7 (14%) of dengue encephalitis and 1 (2%) of case of human immunodeficiency virus encephalitis. Only 5 (10%) cases had bacterial etiology. Those who needed inotropes and mechanical ventilation showed significant mortality. Conclusion: The peak of AES cases occurred during the monsoon period. A higher proportion of such cases had viral etiology on cerebrospinal fluid analysis. Use of inotropes and mechanical ventilation was identified to be associated with significant mortality.